Study of effects of electron irradiation on the nano-p articles in al-zn alloy by small angle neutron scattering - Baig, M.R.; Garawi, M.S.; Farooq, W.A.; Yakuphanoğlu, Fahrettin (My University, 2012)
The effects of 2 MeV electron irradiation on the nano particles in a room temperature aged Al-Zn alloy have been studied using small angle neutron scattering (SANS). A series of electron irradiation was performed on each sample and SANS measurements were made on the PLUTO small angle neutron scattering instrument (U.K) after each irradiation. In general for low doses the results show an initial decrease in the magnitude of the scattering, but associated with an increase in the size of the nano particles. This is followed on prolonged irradiation by an increase in the magnitude of the scattering with a continued increase of nano particle sizes. It is believed that at low doses some nano particles swell but others dissolve, the matrix is then supersaturated and with the enhanced rate of diffusion. As a result of irradiation, the remaining nano particles grow rapidly. As the super saturation reduces a coarsening mechanism takes over, via a radiation enhanced diffusion mechanism. © IDOSI Publications, 2012.
Keywords: Coarsening; G-p zones; Nano- particles; Scattering length density; Small angle Neutron scattering